An update on the pharmacology, phytochemistry, and toxicity of Myristica fragrans Houtt. as a source of treatment: A scoping review - Hilal Yaafi Elfia, Susilo Susilo (Journal of Applied Pharmaceutical Science, 2023)
Myristica fragrans (Houtt.) or nutmeg is reported to have many implementations in traditional medicine, and it possesses fragrance properties. The literature has recently shown scientific interest in health-promoting agents expected to make cost-effective therapeutic agents. This review aims to systematically review articles related to nutmeg’s phytochemical, pharmacological, and toxicity activity. Information was collected by searching the Springer, Scopus, Taylor and Francis, ScienceDirect, ProQuest, SAGE, Wiley, and PubMed databases using Preferred Reporting Items for Systematic Review and Meta-Analyses as per the scoping review guidelines. A total of 28 studies were identified, 2 of which are review studies. There were 15 studies on the pharmacology of different parts of the nutmeg plant; 5 studies focusing on nutmeg phytochemicals; 4 reports related to nutmeg toxicity, including studies presenting case reports; and 4 studies discussing a combination of phytochemicals, pharmacology, and nutmeg toxicity. Overall, nutmeg is a medicinal plant that is claimed to help treat various diseases, including brain nerve disorders, cancer, psychological disorders, cancer, and digestive system disorders. However, further scientific studies are needed to explore individual chemical compounds’ mechanisms of action and therapeutic effects.
Keywords: Biological activity, nutmeg, phytochemistry, pharmacology, toxicity